RANK in cancer-associated fibroblasts: A valuable prognostic determinant for metastasis in early-stage breast cancer patients - Giorello, Maria Belen (2024)
BACKGROUND: The molecular system of receptor activator of nuclear factor kappa-β (RANK) and its ligand (RANKL) plays a role in a variety of physiological and pathological processes. These encompass the regulation of bone metabolism, mammary gland development, immune function, as well as their involvement and tumorigenesis. Nevertheless, limited knowledge exists regarding their function within the tumor microenvironment. METHODS AND RESULTS: We explored the significance of RANK expression in cancer-associated fibroblasts (CAFs) as a prognostic biomarker in early breast cancer patients (BCPs) by immunohistochemistry. Results reveal a significant correlation between high RANK expression in CAFs and an increased risk of metastasis (p = 0.006), shorter metastasis-free survival (MFS) [p = 0.007, OR (95%CI) = 2.290 (1.259–4.156)], and lower overall survival (OS) [p = 0.004, OR (95%CI) = 2.469 (1.343– 4.541)]. Upon analyzing the phenotype of CD34(-) CAFs isolated from primary tumors in BCPs, we observed co-expression of RANK with CD105 marker by immunofluorescence and flow cytometry, characteristic of mesenchymal stem/stromal cells (MSCs), suggesting the possible cellular origin. Also RANKL-RANK system increase the OCT-4, SOX-2 and DKK-1 (dickkopf 1) gene expression in CD34(-) CAFs by RT-PCR. Moreover, this system plays a crucial role in the migration of these CD34(-) CAFs. CONCLUSIONS: These results support the clinical relevance of RANK in CAFs and propose its potential as a future therapeutic target in the treatment of early BCPs.